Support Of Excavation System - Columbia Heights Metro Station Project - Washington, D.C. - Summary: - Robert W. Bergwall (Deep Foundations Institute, 1997)
The $58,000,000.00 Columbia Heights Metro Station project (Section E3-a) forms a part of the Washington Metropolitan Area Transit Authority's (WMATA) Greenbelt Route - Green Line subway system. The Greenbelt route is one often segments that make up WMATA's subway system. Construction of the "cut and cover" reinforced concrete station includes 600 linear feet of an underground center platform, two ancillary service areas totaling 466 linear feet, two surface entrances, and vent shafts (See Figure No. 1). Station subgrade is approximately 60 feet below existing grade. The project can be divided into five main areas: 1. North Service Rooms and Passageway; 2. West Entrance and West Passageway; 3. East Entrance; 4. Center Platform; 5. South Service Rooms. Station dimensions are approximately 1068 feet long by 64 feet wide. Construction commenced at the site in January of 1995 and is expected to be completed by December of 1999. Franki Northwest Company, Crofton, Maryland, was awarded a subcontract by general contractor Blake Construction Company, Washington, D.C, to install the support of excavation and temporary decking systems. Franki's scope of work included the installation of 490 drilled soldier piles plus two elevator shafts totaling 29,700 linear feet of drilling; 1,150 tons of steel decking covered by 37,000. square feet of precast concrete deck planks; 120,000. square feet of timber lagging; 2,500. tons of struts and wales; and temporary support of underground utilities. In conjunction with Franki's work, Bencor Corporation of America, Dallas, Texas, constructed parallel, 600 foot long slurry walls which serve as permanent walls for the center platform portion of the station.